Thermomechanical process modelling of 40NICRMO8-4 alloy by artificial neural networks - Alibeiki, Esmaeil; Rajabi, Jamal; Rajabi, Javad (Penerbit Universiti Kebangsaan Malaysia, 2019)
Artificial neural networks (ANNs) as simplified model of mankind’s neural system, are capable of simulating and predicting real world complex problems which are challenging and expensive to model physically. In this study the correlation between the flow stresses and strain rate, temperature, strain in thermomechanical process of 40NICRMO8-4 alloy has been modelled. The results revealed that flow stress for every strain value is less at high temperatures compared to those at low temperatures and material resistance against deformation will also decrease as temperature goes down. Moreover, increasing in strain rate when temperature is constant results in recrystallization to happen in higher strain values at times shorter. The employed neural network for this study was a feed forward multilayer perceptron trained with common back propagation algorithm. Similar to any other ANNs, the employed network receives some parameters as inputs and delivers some as outputs. The inputs given to this model were temperature, strain and strain rate while flow stress parameter was collected as requested output. Outputs, with high precision of approximately 99% accuracy, were predicted and produced during training phase. Likewise, the predicted output of the ANN model achieved an R-value of about 0.99871 compared with of those experimental values. Best results were obtained with an ANN model consist of two hidden layers trained with Levenberg–Marquardt training algorithm.